Intergenerational Mobility: An Assessment for Latin American Countries - Ömer Tuğsal Doruk; Hasan Bilgehan Yavuz; Francesco Pastore (Global Labor Organization (GLO), 2019)
This paper aims to study the process of intergenerational income mobility in some Latin American economies (Panama and Brazil), which have been much neglected in the existing literature. Like other countries in the area, also Brazil and Panama have a stagnant economy coupled with high income inequality. Our rich and detailed dataset, the IPUMS survey data bank allows us to provide the most reliable and robust estimates of intergenerational transfer, after controlling for a number of additional control variables which were unavailable in previous studies, such as family size, literacy level of fathers, and location in rural versus urban areas. We provide estimates broken down for different genders, age, location, education of fathers in each country. Our results are robust to different specifications and suggest that previous studies significantly overrated the extent of the intergenerational transfer in the countries considered. However, our figures are still compatible with an extremely low degree of social mobility.
Keywords: J62; J60; D3; D6; 330; Intergenerational mobility; Occupational mobility; Latin American Economies